Fear of COVID-19 and Remote Teaching Burnout of Filipino K to 12 Teachers - Carreon, Thalia; Rotas, Erwin; Cahapay, Michael; Garcia, Kenneth; Amador, Romina; Anoba, Jeorge Louie (IJERI: International Journal of Educational Research and Innovation, 2021)
The COVID-19 crisis practically magnified the normal fear of people, bringing other negative psychological outcomes such as job burnout. Building on this assumption, this paper aimed to compare fear of COVID-19 and remote teaching burnout across sample characteristics and relate fear of COVID-19 to the remote teaching burnout. Following comparative and correlational research designs, a sample of 1069 K to 12 Filipino teachers was selected to participate in the online survey. The data were analyzed using descriptive and inferential statistics. The results showed that the teachers have a high level of fear of COVID-19 and a moderate level of remote teaching burnout. Furthermore, COVID-19 fear of teachers did not significantly differ across all sample characteristics tested; however, remote teaching burnout significantly differed across age, monthly income, educational attainment, and teaching experience, except gender. It was further revealed that there is a positive and moderate significant relationship between fear of COVID-19 and remote teaching burnout. This linear association implies that as fear of COVID-19 of teachers increases, their remote teaching burnout also increases. Considering the current persistence of COVID-19 cases and the role of teachers in the anticipated recovery phase of education, the results of the study indicate the urgent attention of education authorities to develop measures to address the needs of teachers who may have psychological issues brought by fear of COVID-19 and remote teaching burnout.